THE RELATIONSHIP BETWEEN THE FREQUENCY OF CONSUMPTION OF JUNK FOOD AND CONTEMPORARY DRINKS IN STUDENTS AT SMA SEJAHTERA 1 DEPOK - Fairuz Mufidah; Siti Riptifah Tri Handari; Rusman Efendi; Nurmalia Lusida (Muhammadiyah International Public Health and Medicine Proceeding, 2024)
An indication of the body's adequate dietary intake and nutrient use is called nutritional status. Teenagers who are overweight face significant challenges. According to the 2018 West Java Province Health Profile, 10.9% of adolescents aged 16 to 18 were overweight, and 4.5% were obese. The district with the greatest prevalence of overnutrition, Depok, had an 18.1% prevalence. With a population of SMA Sejahtera 1 Depok pupils and a sample of 97 individuals chosen through purposive sampling, this study employed a cross-sectional design. Weight and height measurements were used to measure the dependent study variable, nutritional status, and a questionnaire was used to measure the independent variable. computer software for univariate and bivariate data analysis (Chi-Square test). According to the study's findings, 60.8% of respondents had better nutritional status. The frequency of consuming junk food (p-value = 0.704), modern beverages (p-value = 1.000), and nutritional status are unrelated. The conclusion is that there is no relationship between the frequency of consumption of junk food and the nutritional status of students, but teens who frequently consume junk food and modern beverages are more likely to be overweight or obese. Recommendations for students to focus more on their health and to watch what they eat and drink, avoiding contemporary drinks and junk food too frequently.